2016
DOI: 10.3390/molecules21070898
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Costunolide against Hydrogen Peroxide-Induced Injury in PC12 Cells

Abstract: Abstract:Oxidative stress-mediated cellular injury has been considered as a major cause of neurodegenerative diseases including Alzheimer's and Parkinson's diseases. The scavenging of reactive oxygen species (ROS) mediated by antioxidants may be a potential strategy for retarding the diseases' progression. Costunolide (CS) is a well-known sesquiterpene lactone, used as a popular herbal remedy, which possesses anti-inflammatory and antioxidant activity. This study aimed to investigate the protective role of CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Oxidative stress-mediated cellular injury is a major cause of neurodegenerative diseases, and PC-12 cells have been applied for model construction in analysing the molecular mechanism of SCI in vitro [21][22][23]. Moreover, SCI is reported as a fearful neurology-related disease and the latent therapeutic strategies for this injury have been grabbed in PC-12 cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress-mediated cellular injury is a major cause of neurodegenerative diseases, and PC-12 cells have been applied for model construction in analysing the molecular mechanism of SCI in vitro [21][22][23]. Moreover, SCI is reported as a fearful neurology-related disease and the latent therapeutic strategies for this injury have been grabbed in PC-12 cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…In ancient times, people thought the root of this plant has the function of promoting the circulation of blood and relieving pain [8]. It was reported that costunolide could inhibits proliferation, arrests cell cycle and induces apoptosis of many cancers, such as breast cancer, colon cancer, bladder cancer, prostate cancer and hepatocellular carcinoma cells [9][10][11][12][13][14][15][16][17]. However, the research on GC inhibited by costunolide is relatively few.…”
Section: Introductionmentioning
confidence: 99%
“…PC12 cells, which derive from a rat pheochromocytoma and possess neuron-like characteristics, have been applied for construction of useful model system in analyzing the neurological apoptosis [19]. SCI is a severe neurological disease, and mounting researches have used PC12 cells as important adjuncts and surrogates for studies of SCI in humans [20,21].…”
Section: Original Papermentioning
confidence: 99%